2021
DOI: 10.21511/bbs.16(3).2021.05
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the efficiency of the monetary transmission mechanism channels in Ukraine

Abstract: The paper is focused on the performance features of the monetary transmission mechanism (MTM) in Ukraine as a small open economy. To assess the efficiency of monetary transmission channels, it is important to disclose their interaction, define criteria and tools for analyzing their impact on key macroeconomic parameters. The study deepens approaches to the analysis of the intensity of using monetary, credit, interest rate and exchange rate channels in Ukraine in 2005–2020 and detects violations in the function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…With regard to accounting, the work emphasizes the need to reflect all economic transactions in accounting and financial reporting, especially those that indicate a decrease in value or destruction of assets as a result of hostilities. The results of the study confirm that the international standards of accounting and financial reporting contain principles regarding the disclosure of information in cases of negative impact of military actions on the property and monetary assets of enterprises (Yaroshenko et al, 2019;Mishchenko et al, 2021). The importance of the reliability of the reflection of all economic transactions in the activities of enterprises, both during the period of martial law and during the normal period, is emphasized by Ukrainian scientists V. Mukoviz et al (2022), who considered the role of transaction costs, i.e., costs associated with negotiations, drawing up contracts and concluding agreements, monitoring their im-plementation, and their impact on the growth of shadow operations at agribusiness enterprises.…”
Section: Discussionsupporting
confidence: 63%
“…With regard to accounting, the work emphasizes the need to reflect all economic transactions in accounting and financial reporting, especially those that indicate a decrease in value or destruction of assets as a result of hostilities. The results of the study confirm that the international standards of accounting and financial reporting contain principles regarding the disclosure of information in cases of negative impact of military actions on the property and monetary assets of enterprises (Yaroshenko et al, 2019;Mishchenko et al, 2021). The importance of the reliability of the reflection of all economic transactions in the activities of enterprises, both during the period of martial law and during the normal period, is emphasized by Ukrainian scientists V. Mukoviz et al (2022), who considered the role of transaction costs, i.e., costs associated with negotiations, drawing up contracts and concluding agreements, monitoring their im-plementation, and their impact on the growth of shadow operations at agribusiness enterprises.…”
Section: Discussionsupporting
confidence: 63%
“…Researchers concluded that in the crisis caused by the COVID-19 coronavirus pandemic, banks with international investment demonstrated the greatest efficiency, while those controlled by domestic capital demonstrated the least efficiency. According to the researchers, the situation could be effectively resolved through the privatization of state-owned banks in Ukraine with the involvement of international investors (Mishchenko et al, 2021). The findings of the scientists, while not in obvious contradiction with the results of this research, significantly complement them in the context of the assessment of risk factors in the banking environment as exemplified by Ukraine.…”
Section: Discussionmentioning
confidence: 55%
“…Obviously, a correct assessment will not be possible without a proper understanding of the mechanisms by which monetary policy will affect economic variables. One of the important advances in the field of monetary transmission mechanism studies in recent years has been the identification of financial market conditions and their progress as one of the environmental factors affecting the monetary transmission mechanism and the effect of fiscal policy is different in different countries [ 39 ].…”
Section: Introductionmentioning
confidence: 99%